2021
DOI: 10.21203/rs.3.rs-141245/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Comprehensive Analysis of COVID-19 Impact in Latin America

Abstract: Background: Latin America has now become the epicenter of the global coronavirus disease 2019 (COVID-19) pandemic. In the ongoing COVID -19 pandemic, a profound burden of SARS-COV-2 infection has been reported in Latin America. In the present study, we aim to determine the profiles that are associated with this disease in Latin America. We analyzed symptoms, morbidities and gastrointestinal (GI) manifestations by country.Methods: We analyzed data from SARS-CoV-2 positive patients evaluated at healthcare center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…The percentage of women's participation (56.2%) was lower here than in the study carried out in Spain, with psychological distress was also lower in women in Peru than in Spain, and, similar to most countries investigated, higher psychological distress was found among women than in men [17,18]. It is known that sex is a variable that influences the level of COVID-19 contagion and, in a study on people assisted with COVID-19 conducted in eight Latin American countries, Peru presented a higher percentage of women [4]. In the present study, higher psychological distress has also been found among younger people, but, on the contrary, higher psychological distress was found among those with the lowest level of education.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…The percentage of women's participation (56.2%) was lower here than in the study carried out in Spain, with psychological distress was also lower in women in Peru than in Spain, and, similar to most countries investigated, higher psychological distress was found among women than in men [17,18]. It is known that sex is a variable that influences the level of COVID-19 contagion and, in a study on people assisted with COVID-19 conducted in eight Latin American countries, Peru presented a higher percentage of women [4]. In the present study, higher psychological distress has also been found among younger people, but, on the contrary, higher psychological distress was found among those with the lowest level of education.…”
Section: Discussionsupporting
confidence: 43%
“…Moreover, the level of compliance and differences between population groups according to socioeconomic, educational, and working conditions are variables that are known to determine physical and mental health. This requires reliable sources of information, something that has been highly questioned as seen in previous studies [4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations